Substantial Impact of COVID-19 on Self-Reported Mental Health of Healthcare Professionals in the Netherlands - de Vroege, Lars; van den Broek, Anneloes (Frontiers in Public Health, 2022)
Initially, the COVID-19 pandemic caused a continued pressure on professionals working in hospitals due to the increase of affected patients. At the moment, the pandemic continues but thanks to all kinds of measures (e.g., social distancing) workload seems to decrease at the hospitals. On the contrary, patients with long-lasting symptoms due to COVID-19 infection or the pandemic begin to merge at the mental healthcare institutions in the Netherlands but this also holds true for other countries. Furthermore, healthcare professionals are affected by safety measures such as working from home, which led to an increased feeling of stress and may have led to a misbalance in work and private life. As a result, the question whether healthcare employees in mental healthcare experience impaired mental health remains unclear and chances are fair that mental health problems such as exhaustion and burnout may be prevalent. This study describes an online survey in which mental health amongst mental healthcare professionals is investigated. About 1,300 professionals from a large number of mental healthcare institutions replied the survey. Around 50% of the respondents experienced increased levels of stress. Feelings of anxiety, anger, and sadness were also increasingly experienced due to the COVID-19 pandemic. Furthermore, 4.2% replied that they were considering resigning their jobs which is alarming considering the shortage of healthcare professionals in mental healthcare institutions. The results support the importance of treatment or support of professionals in mental healthcare that experience psychological ailments.